Deconstruction After 9/11. - McQuillan, Martin (Routledge Research in Cultural and Media Studies, 10., 2008)
The book as a whole follows a double thread: offering a series of critical-theoretical commentaries on geopolitical events from the Kosovan conflict to the Iraq war, combined with a sustained analysis of the political thought of Jacques Derrida as it appears in his writing since Specters of Marx.